1995
DOI: 10.1104/pp.107.3.737
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Enhancement of Oxidative Stress Tolerance in Transgenic Tobacco Overexpressing Manganese Superoxide Dismutase in the Chloroplasts

Abstract: Two varieties of tobacco (Nicofiana fabacum var PBD6 and var SR1) were used to generate transgenic lines overexpressing Mnsuperoxide dismutase (MnSOD) in the chloroplasts. The overexpressed MnSOD suppresses the activity of those SODs (endogenous MnSOD and chloroplastic and cytosolic Cu/ZnSOD) that are prominent in young leaves but disappear largely or completely during aging of the leaves. The transgenic and control plants were grown at different light intensities and were then assayed for oxygen radical stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
130
3
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(144 citation statements)
references
References 31 publications
8
130
3
3
Order By: Relevance
“…This finding runs counter to some previous observations (e.g. Slooten et al 1995, McKersie et al 1999, Kwon et al 2002), on nuclear transformants, which suggest that over-expression of chloroplast-targeted SODs suppresses the activity of the native enzymes, although this finding is far from universal among the various SOD over-expressing lines. In fact there are two publications which support our observation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding runs counter to some previous observations (e.g. Slooten et al 1995, McKersie et al 1999, Kwon et al 2002), on nuclear transformants, which suggest that over-expression of chloroplast-targeted SODs suppresses the activity of the native enzymes, although this finding is far from universal among the various SOD over-expressing lines. In fact there are two publications which support our observation.…”
Section: Discussioncontrasting
confidence: 99%
“…Expression of MnSOD (normally located in the mitochondria, but targeted to the chloroplast in most of these studies) resulted in improved frost tolerance in alfalfa (McKersie et al 1993), cold and oxidative stress tolerance in maize (Van Breusegem et al 1999), drought (Wang et al 2005) and salt tolerance in rice (Tanaka et al 1999), and salt tolerance in poplar (Wang et al 2010). Levels of the Fe or Cu/Zn SODs, normally associated with chloroplasts, have also been enhanced, resulting in improved cold tolerance in alfalfa (McKersie et al 1999(McKersie et al , 2000, salt and drought tolerance (Badawi et al 2004b) in tobacco, and methyl viologen (MV-a superoxide-generating herbicide) tolerance in tobacco (Sen Gupta et al 1993;Slooten et al 1995) and poplar (Arisi et al 1998). Other ROS scavenging enzymes have also attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf antioxidant content varies with growing conditions, and the effect of light intensity has been addressed recently (Slooten, et al, 1995;Grace and Logan, 1996). Plants growing under high light are more frequently exposed to reactive oxygen species (the superoxide radical, H 2 O 2 , and singlet oxygen) generated in the plastids than plants growing at low light intensity, and consequently might respond by accumulating higher amounts of antioxidants in leaf tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes such as SOD, GR, ASPX, and DAS reductase, and com-pounds such as ascorbate and glutathione are actively involved in the ascorbate-glutathione scavenging cycle, controlling reactive oxygen species not only in the chloroplast but also in the cytosol (for reviews, see Alscher and Hess, 1993;Foyer and Mullineaux, 1994). The involvement and role of antioxidants in protection against oxidative stress have been demonstrated using transgenic plants (Foyer et al, 1994;Allen, 1995;Slooten et al, 1995), and genetic variability in the content of antioxidant elements has been reported in several species (Sevilla et al, 1988;Daza et al, 1993;Guzy and Heath, 1993). Tolerance of oxidative stresses such as the herbicide paraquat and NaCl were partially associated with a better antioxidant response in tolerant genotypes (Gossett et al, 1994;Hernández et al, 1995).…”
mentioning
confidence: 99%
“…For example, a decrease in the activity of the key antioxidant enzymes caused by shading resulted in the disappearance of the beneficial effect of MnSOD overproduction on the methyl viologen resistance of transgenic tobacco plants (Slooten et al 1995). The overproduction of SOD itself can cause an increase in the activity of other antioxidant enzymes (Sen Gupta et al 1993a, b;Kingston-Smith and Foyer 2000); however, this effect is not always observed (Payton et al 2001).…”
Section: Transgenic Manipulations Of Photoprotectionmentioning
confidence: 99%